Targeting the chemokines in acute graft-versus-host disease - Xu, Ziwei; Wang, Huafang (Frontiers in Immunology, 2025)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) constitutes a critical therapeutic approach for patients with malignant hematological disorders. Nevertheless, acute graft-versus-host disease (GVHD), one of the most prevalent complications associated with HSCT, remains a leading contributor to non-relapse mortality. In recent years, there has been an increasing focus on the interplay between chemokines and their receptors in the context of acute GVHD. Chemokines exert substantial effects across various pathological conditions, including autoimmune diseases, inflammatory processes, tumorigenesis, and metastatic dissemination. In this review, we aim to elucidate the role of chemokines in the pathogenesis of acute GVHD and further understand their potential as diagnostic biomarkers. We also present both preclinical and clinical insights into the application of chemokines in preventing and treating acute GVHD. The objective of this review is to offer novel perspectives on the clinical diagnosis and management strategies for acute GVHD.